Plasmodesmata act as unconventional membrane contact sites regulating intercellular molecular exchange in plants - Pérez-Sancho, Jessica; Smokvarska, Marija; Dubois, Gwennogan; Glavier, Marie; Sritharan, Sujith; Moraes, Tatiana S.; Moreau, Hortense; Dietrich, Victor; Platre, Matthieu P.; Paterlini, Andrea; Li, Ziqiang P.; Fouillen, Laetitia; et al. (Cell, 2025)
Membrane contact sites (MCSs) are fundamental for intracellular communication, but their role in intercellular communication remains unexplored. We show that in plants, plasmodesmata communication bridges function as atypical endoplasmic reticulum (ER)-plasma membrane (PM) tubular MCSs, operating at cell-cell interfaces. Similar to other MCSs, ER-PM apposition is controlled by a protein-lipid tethering complex, but uniquely, this serves intercellular communication. Combining high-resolution microscopy, molecular dynamics, and pharmacological and genetic approaches, we show that cell-cell trafficking is modulated through the combined action of multiple C2 domains transmembrane domain proteins (MCTPs) 3, 4, and 6 ER-PM tethers and phosphatidylinositol-4-phosphate (PI4P) lipid. Graded PI4P amounts regulate MCTP docking to the PM, their plasmodesmata localization, and cell-cell permeability. SAC7, an ER-localized PI4P-phosphatase, regulates MCTP4 accumulation at plasmodesmata and modulates cell-cell trafficking capacity in a cell-type-specific manner. Our findings expand MCS functions in information transmission from intracellular to intercellular cellular activities. [Display omitted] •Plasmodesmata are unconventional ER/PM contact sites located at cell-cell interfaces•Plasmodesmata operate as control valves, modulating ER-PM contacts to regulate transport•MCTP3, MCTP4, MCTP6, and PI4P tethering elements act as valve regulators•SAC7 PI4P phosphatase controls plasmodesmata MCS in a cell-type-specific manner Plant intercellular communication is regulated via tubular ER-PM membrane contact through PI4P and MCTP protein tethers.